The Less Expensive Choice: Bacterial Strategies to Achieve Successful and Sustainable Reciprocal Interactions - Pessione, Enrica (Frontiers in Microbiology, 2021)
ABSTRACT Bacteria, the first organisms appeared on Earth, continue to play a central role in ensuring life on the planet, both as biogeochemical agents and as higher organisms’ symbionts. In the last decades, they have been employed both as bioremediation agents for cleaning polluted sites and as bioconversion effectors for obtaining a variety of products from wastes (including eco-friendly plastics and green energies). However, some recent reports suggest that bacterial biodiversity can be negatively affected by the present environmental crisis (global warming, soil desertification, ocean acidification). This review analyzes the behaviors positively selected by evolution that render bacteria good models of sustainable practices (urgent in these times of climate change and scarcity of resources). Actually, bacteria display tendency to optimize rather than maximize, to economize energy and building blocks (by using the same molecule for performing multiple functions), to recycle and share metabolites, and this are winning strategies when dealing with sustainability. Furthermore, their ability to establish successful reciprocal relationships by means of anticipation, collective actions and cooperation, can also constitute an example highlighting how evolutionary selection favors behaviors that can be strategic to contain the present environmental crisis.